Telocytes in their context with other intercellular communication agents. (July 2016) - Edelstein, Lawrence; Fuxe, Kjell; Levin, Michael; Popescu, Bogdan O.; Smythies, John
Abstract: The past decade has borne witness to an explosion in our understanding of the fundamental complexities of intercellular communication. Previously, the field was solely defined by the simple exchange of endocrine, autocrine and epicrine agents. Then it was discovered that cells possess an elaborate system of extracellular vesicles, including exosomes, which carry a vast array of small and large molecules (including many epigenetic agents such as a variety RNAs and DNA), as well as large organelles that modulate almost every aspect of cellular function. In addition, it was thought that electrical communication between cells was limited mainly to neurotransmitters and neuromodulators in the nervous system. Also within the past decade, it was found that – in addition to neurons – most cells (both mammalian and non-mammalian) communicate via elaborate bioelectric systems which modulate many fundamental cellular processes including growth, differentiation, morphogenesis and repair. In the nervous system, volume transmission via the extracellular matrix has been added to the list. Lastly, it was discovered that what had previously been regarded as simple connective cells in most tissues proved to be miniature communication devices now known as telocytes. These unusually long, tenuous and sinuous cells utilize elaborate electrical, chemical and epigenetic mechanisms, including the exchange of exosomes, to integrate many activities within and between nearly all types of cells in tissues and organs. Their interrelationship with neural stem cells and neurogenesis in the context of neurodegenerative disease is just beginning to be explored. This review presents an account of precisely how each of these varied mechanisms are relevant and critical to the understanding of what telocytes are and how they function.